2002
DOI: 10.1182/blood.v100.2.467
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-E2 enhances EPO-mediated STAT5 transcriptional activity by serine phosphorylation of CREB

Abstract: Erythroid colony formation in response to erythropoietin (EPO) stimulation is enhanced by costimulating the cells with prostaglandin-E 2 (PGE 2 ). The present study further analyzed the underlying mechanisms and demonstrated that EPOmediated STAT5 transactivation in the erythroid AS-E2 cell line was enhanced 6-fold by PGE 2 (10 M), without affecting the STAT5 tyrosine phosphorylation or STAT5-DNA binding. Moreover, the PGE 2 -enhancing effect was independent of STAT5 serine phosphorylation. In AS-E2 cells STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
1
35
1
Order By: Relevance
“…In contrast to our results, expression level of SOCS3 mRNA induced by PGE 2 is lower than those induced by IL-10. Also another report demonstrated that PGE 2 increases erythropoietin-dependent STAT5 regulatory genes, such as SOCS3 (31). This costimulatory effect of PGE 2 on erythropoietin-mediated STAT5 transactivation is mediated by the cAMP/PKA/CREB pathway, without affecting the STAT5 tyrosine phosphorylation or STAT5 DNA binding.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast to our results, expression level of SOCS3 mRNA induced by PGE 2 is lower than those induced by IL-10. Also another report demonstrated that PGE 2 increases erythropoietin-dependent STAT5 regulatory genes, such as SOCS3 (31). This costimulatory effect of PGE 2 on erythropoietin-mediated STAT5 transactivation is mediated by the cAMP/PKA/CREB pathway, without affecting the STAT5 tyrosine phosphorylation or STAT5 DNA binding.…”
Section: Discussionmentioning
confidence: 89%
“…In the presence of Epo, Signal transducer and activator of transcription 5 (STAT5) is recruited to the Epo receptor and phosphorylated by the Janus kinase 2 (JAK2). Once phosphorylated, STAT5 is released from EpoR, homodimerizes in the cytosol, and translocates to the nucleus where it activates its target gene expression, including Bcl-X and cyclin D1 (53)(54)(55)(56)(57)(58). Phosphorylation of CREB by PKA enhances Epo-stimulated STAT5 transactivation by inducing recruitment of CREB/CBP/p300 to the STAT5 transactivational complex (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…In erythrocytes and neuronal cells, EPO and EPO-R stimulation can activate protein kinase cascades (15,42,43). The primary kinase signaling pathway is the stress-responsive Jak2, which can lead to phosphorylation and activation of several downstream targets, including the transcription factor STAT5 (42).…”
Section: Discussionmentioning
confidence: 99%
“…The primary kinase signaling pathway is the stress-responsive Jak2, which can lead to phosphorylation and activation of several downstream targets, including the transcription factor STAT5 (42). Jak-STAT signaling is involved in prevention of neuronal apoptosis (15) and interestingly, the Jak-STAT pathway has recently been shown to play a role in cardiac ischemic preconditioning, thereby reducing ischemic damage to the heart (44).…”
Section: Discussionmentioning
confidence: 99%